Patient care costs in the state training and research hospitals in Istanbul in years 2000-2007 - BAKOĞLU, REFİKA (My University, 2011)
The application of neoliberal policies that began to spread all over the world and Turkey at least since 1980s as it is commonly accepted. The latest applications of the neoliberal policies mainly observed in the service sector and especially in the health sector. After the year 2000, the important reforms in health sector has been applied by the Ministry of Health in Turkey like "privatization", "autonomy", "decentralization", "family medicine" and "general health insurance" implementations. These research aims to find out how these implementations of the neoliberal policies in health sector affect the treatment costs of the patients in public research and training hospitals in Istanbul, Turkey, which represent 60% of the hospitals in Istanbul. Document analysis has been applied in order to figure out the effect. There is time limitation in the research due to the time limitations and difficulties in reaching the old documents. This study is valid for the years 2000 and 2007, and 2003 is accepted as the turning point since the implementations of the neoliberal policies in health care industry in Turkey has been put into practice at the time. The treatment services given in public hospitals and the changes in these services and in treatment expenses were analyzed from the 7253 invoices of the patients that were treated at Lütfi Kirdar Educational and Research Hospital and şişli Etfal Educational and Research Hospital. The invoices of the patients were separated into: laboratory, drugs, medical materials, radiologic studies and general services, and respectively into: price, procedure numbers, costs per procedure, and the percentage of each costs in the invoices for two periods as the years 2000-2003 (first/pre-implementation period) and 2004-2007 (second/post-implementation period). The expenses were separated into price, procedure numbers, costs per procedure, and the percentage of each cost in total, and the two periods were compared to observe whether there is a difference pre-implementation and post-implementation periods of the neoliberal policies in the health sector. © 2011 Published by Elsevier Ltd.